Reliability of the maximal oxygen uptake following two consecutive trials by indirect calorimetry - Hall López, Javier Arturo (2015)
Background: The maximal oxygen uptake (VO2máx) assessment by indirect calorimetry is the most reliable method to determine VO2máx, but when repeated tests are conducted, the results have been controversial. Aim: To determine the reliability of the maximal oxygen uptake (VO2máx) in healthy adults following two consecutive trials with 10 min rest between trials using the Bruce protocol. Methods: Participants were 6 males apparently healthy physically active (Mean age=23,4±1,3 years), who performed twice the Bruce protocol and after reaching their VO2máx in the first trial they stepped down the treadmill and rested seated on a chair during 10 min. Results: The data analysis showed high reproducibility values between tests, indicated by the correlation coefficient Pearson product moment and R squared with confidence intervals at 95% (CI95%), the correlation of the maximum oxygen consumption was VO2máx =0.907 with a R2=0.823, the maximum heart rate was HRmáx=0.786, with R2=0.618 and the rate of ventilation and carbon dioxide elimination was VE/VCO2=0.868, with an R2=754. No adverse effects were reported during the 10 min rest between trials. Conclusion: Resting 10 min between consecutive maximal exercise tests using Bruce protocol treadmill tests does not affect VO2máx in healthy young adults. It is feasible and reliable to perform maximal treadmill tests in a single session without adverse effects for the participant.